Marketing Strategies Application Problems in Lithuanian Life Insurance Services Market - Kindurys, Vytautas (Ekonomika, 2003)
Lithuanian life insurance services market is in development stage in meanwhile. Though competitiveness increases in it. It is more difficult for new companies to enter to this market. Companies that achieve to act successfully in Lithuanian life insurance services market have to prepare corresponding marketing strategies. This article first presents theoretical marketing strategies application aspects in life insurance services market. It enumerates marketing strategies. which can be applied in Lithuanian life insurance services market, basing on other separate authors opinion. Article presents definitions of these strategies and describes analysis of their application cases. Article presents analysis of Lithuanian life insurance services providers market structure and their competitiveness. 9 life insurance companies act in comparing small Lithuanian life insurance services market. Lithuanian life insurance services providers market concentration level decreasing tendency tells about growing more active competitiveness in this market. Lithuanian life insurance services market becomes close to oligopoly market structure. Characteristic features of this kind of market arc these: dominant one group of insurance companies whose dominancy in market decreases; increases competitive role of two separate insurance companies; comparing big market concentration: five insurance companies from nine occupy even 97 percent of market; it is difficult for new companies to enter this market (big costs of entering the market). As a matter of fact companies practice penetration and services development marketing strategies in lithuanian life insurance services market. Corresponding life insurance companies apply market leader and market pretender marketing strategies. Lithuanian life insurance companies not enough attention pay to strategic marketing planning, marketing research and customer market segmentation so far. Some Lithuanian life insurance companies managers marketing strategies form leaning upon intuition.